Understory growth of Paris polyphylla accumulates a reservoir of secondary metabolites of plants - Yan, Xinru; Wang, Dong; Zhang, Ao; Xia, Jing; Jiao, Jinlong; Ghanim, Murad; Xiaokun, Ou; He, Xiahong; Shi, Rui (Frontiers in Microbiology, 2024)
Paris polyphylla is an important traditional medicinal plant of the Himalayan region. It is extensively used for the production of natural steroidal saponins and flavonoids. Although seed dormancy of wild plants can be broken to be artificially maintained and regenerated through micropropagation in the laboratory, the success of secondary metabolite production in higher quantities and the synthesis of superior plant metabolites have been very limited. In this study, we present differential metabolic profiling of P. polyphylla plants maintained for 8 years in natural and greenhouse conditions. Untargeted profiling of the metabolites through ultra-performance liquid chromatography-mass spectrometry/mass spectrometry (UPLC-MS/MS), followed by statistical analysis, identified secondary metabolites that were enriched in the naturally occurring plant roots compared with the greenhouse plant roots. A multivariate statistical analysis revealed the differential distribution of the compounds between the two groups. Overall, we identified 1,182 secondary metabolites, with 116 metabolites being differentially upregulated and 256 metabolites being downregulated. Moreover, 810 metabolites showed no significant variation under both growing conditions. The Kyoto Encyclopedia of Genes and Genomes (KEGG) analysis revealed that the naturally forest-grown P. polyphylla plants were significantly enriched in steroidal saponins, lipids, vitamins, flavonoids, and flavonols. An analysis of the top 10 differentially upregulated secondary metabolites indicated a significantly enriched quantity of spirost-5-en-3,12-diol and kaempferol synthesis pathways, which are known to reduce the effect of free radicals scavengers inside the cell. In addition, veratramine alkaloids were also enriched under natural conditions. Our findings indicated that naturally maintained P. polyphylla plants are suitable for the extraction of medicinally important compounds. Our study established a causal relationship between the metabolic composition of the roots and their natural growth condition. This study highlighted the importance of environmental conditions in the biosynthesis of secondary metabolites of plants.